Uso De Un Polímero Hidrófilo A Base De Poliacrilamida Para Mejorar La Eficiencia En El Uso Del Agua - López-Elías, Jesús; Garza O., Sergio; Jiménez L., José; Huez L., Marco Antonio; Garrido L., Oscar Damián (European Scientific Journal, ESJ, 2016)
As an alternative in search of new options to reduce overexploitation of groundwater that allow us to increase agricultural profitability in water scarce areas, the behavior of a commercial hydrophilic polymer based in polyacrylamide (PAM) Lluvia solida®, was analyzed by evaluating the polymer hydration capacity. The tests that we used showed that this polymer is capable of absorbing its own weight in 268 times when using distilled water. When salts are dissolved in the water, the polymer reduces its water absorbing capacity, the hydration capacity being lower as the salt content increases, with a water absorption reduction up to 116 times its weight. The polymer hydration capacity also decreases significantly when a complete nutritive solution is used, reducing water absorption up to 55 times its weight; in the presence of divalent (Ca2+ and Mg2+) and monovalent (K+ and NH4 +) cations the polymer hydration capacity reduces proportionally to the cation concentration as an exponential function. Urea did not have any effect in the polymer hydration, thus this fertilizer may be used along with the polymer. The use of this hydrophilic polymer is a tool that improves the water use efficiency but the effect depends on water quality, being reduced by the presence of salts in water.